부산지역 목회자의 교구간호사업 요구조사 - 손수경(Sue Kyung Sohn); 강경자(Kyung Ja Kang); 이지현(Ji Hyun Lee); 이영은(Young Eun Lee); 박춘화(Choon Hwa Park) (지역사회간호학회지, 2002)
The purpose of this study was to provide the basic resources for developing a parish nursing program. We did this by investigating what demands were made on the parish nursing service by the parishes or churches under review. The subjects of this study were 96 pastors located throughout the City of Busan. NP (New paragraph) $\gg$ We conducted our research by utilizing a modified version of the study created by Hwang (2000) and by using the help of prior research and professionals gathered from the parish nurse questionnaire by Djupe (1990). The data in this study were collected from July 1 to Oct. 31, 2001, using the questionnaire method. The Data were analyzed by: (a) frequency: (b) percentage: (c) mean: (d) standard deviation, and x^2-test$ with SPSS/PC program. The study has found the follows: 1. For subjects making demands on the parish nursing service, 95.8% were in need of using the services of parish nurses. On the demands of parish nursing service for the subjects, 95.8% the necessity of parish nursing services. And they answered by their intention of asking for parish nursing service practice. 2. Of the subjects under review, 71.9% were part-time workers and 28.1% were full-time employees 71.9% of part time and 28.1% of full times duty. In terms of the method of pay for work, 41.8% were pay free or freelance while 51.2% were on salary. And engagement intention of parish nurse as preacher was 88.5%. 3. The demand for nursing services in various categories were as follows. (a) hospice care: (4.02 1.11), (b) health screening: (3.98 1.09), (c) home visiting: (3.97 1.16), (d) group health education: (3.81 1.12), (e) organization of volunteer groups: (3.75 1.12), (f) individual health education: (3.75 1.14), (g) advice on choosing hospital or hospital consultation: (3.69 1.21) and (h) individual counseling: (3.51 1.31). 4. In terms of the specific services rendered by parish nurses. our study found that services were needed for the following: physical symptom management; preparation before death in spiritual preparation for death, blood pressure check in health examination, home visiting where the patient makes phone call, management of chronic disease in group health education, disease management in individual health education, advice on choosing hospital, or hospital consultation: and physical problems in individual counseling. 5. With respect to whether there was a correlation between what church a pastor came from and the types of demands made, there was NO significant difference found. 6. In relation to the characteristics of the subjects and their church and the hope demands (duty pattern and method of payment and engagement intention of parish nurse as preacher) for parish nurses, these had non significant differences. In conclusion, the perception of parish nursing service is very high. Moreover, we found that there is a great demand for well ordered parish nursing services to promote the health of each congregation. Before doing so, it would be better to make things known and to consider the relevant characteristics shown in the researched results.